Power Relations between Kesbangpol and Civil Society Organizations in Electoral Monitoring: A Case Study of the 2024 Presidential Election in East Jakarta - Vanera, Argesthin Ayu; Nurdin, Nurdin (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study addresses the urgent issue of democratic governance in Indonesia, particularly the persistent weaknesses in electoral transparency, accountability, and integrity, as evidenced by increasing violations and declining public trust in recent elections. The research aims to examine the patterns of power relations between the National Unity and Politics Agency (Kesbangpol) and civil society organizations, specifically Pemuda Pancasila and the Forum Komunikasi Anak Betawi (Forkabi), in monitoring the 2024 Presidential Election in East Jakarta, and to assess their influence on electoral credibility and citizen participation. Adopting a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and literature study, then analyzed using thematic analysis. The findings reveal a shift in power dynamics from a hierarchical model to an egalitarian partnership, consistent with the principles of neo-Tocquevillian liberal democracy. This transformation has significantly strengthened civil society’s role as a critical partner of the state in electoral monitoring. The study shows that such collaboration enhances the legitimacy and quality of the election process and serves as a practical model for participatory democratic governance. The practical implication highlights the need for policy development that facilitates cross-sectoral communication, training, and support mechanisms to safeguard electoral integrity and prevent political conflict. The originality of this study lies in its empirical contribution to understanding newly emerging power relations between local government and civil society organizations, shifting away from hegemonic models. By combining field-based evidence, neo-Tocquevillian theory, and a participatory framework, this study offers a novel perspective on the evolving role of civil society in local democratic oversight.